The non-photochemical quenching protein LHCSR3 prevents oxygen-dependent photoinhibition in Chlamydomonas reinhardtii. (16th January 2020) - Roach, Thomas; Na, Chae Sun; Stöggl, Wolfgang; Krieger-Liszkay, Anja
Abstract : At high O2 tensions, as encountered prehistorically, Chlamydomonas reinhardtii elevated levels of NPQ-related proteins and LHCSR3 had an important function in protecting PSI. Abstract: Non-photochemical quenching (NPQ) helps dissipate surplus light energy, preventing formation of reactive oxygen species (ROS). In Chlamydomonas reinhardtii, the thylakoid membrane protein LHCSR3 is involved in pH-dependent (qE-type) NPQ, lacking in the npq4 mutant. Preventing PSII repair revealed that npq4 lost PSII activity faster than the wild type (WT) in elevated O2, while no difference between strains was observed in O2 -depleted conditions. Low F v / F m values remained 1.5 h after moving cells out of high light, and this qH-type quenching was independent of LHCSR3 and not accompanied by losses of maximum PSII activity. Culturing cells in historic O2 atmospheres (30–35%) increased the qE of cells, due to increased LHCSR1 and PsbS levels, and LHCSR3 in the WT, showing that atmospheric O2 tensions regulate qE capacity. Colony growth of npq4 was severely restricted at elevated O2, and npq4 accumulated more reactive electrophile species (RES) than the WT, which could damage PSI. Levels of PsaA (PSI) were lower in npq4 grown at 35% O2, while PsbA (PSII) levels remained stable. We conclude that even at high O2 concentrations, the PSII repair cycle is sufficient to maintain net levels of PSII. However, LHCSR3 has an important function in protecting PSI against O2 -mediated damage, such as via RES.